Smart carpark management - Ang, Rhea Yun Ting (Nanyang Technological University, 2024)
In urban landscapes such as Singapore, persistent challenges such as land saturation and congestion have been longstanding issues. To address these challenges exacerbated by the surge in vehicle ownership, this project focuses on designing and implementing a smart automated parking system tailored for such urban environments. The system aims to optimize space utilization while enhancing user experience through the integration of dynamic algorithms. By streamlining the parking process and alleviating congestion, the automated system offers potential solutions to urban parking challenges. Through a series of experimental simulations, the efficacy and feasibility of the smart parking system are evaluated to assess its potential to enhance urban parking infrastructure in Singapore. Additionally, this project delves into system performance variations, examining factors like physical infrastructure and operational context to better understand their impact on the system's efficiency and effectiveness in addressing urban parking challenges.